PENERAPAN QRIS DALAM MENINGKATKAN GAIRAH LAYANAN PERBANKAN SYARIAH DI SEKTOR UMKM PADANGSIDIMPUAN - Ja'far Nasution; Damri Batubara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the Indonesian Standard QR Code (QRIS) in increasing the enthusiasm for Islamic banking services in the Micro, Small, and Medium Enterprises (MSMEs) sector in Padangsidimpuan City. QRIS, as an integrated digital payment system, is expected to expand access to Islamic financial services in an inclusive and efficient manner. The research method used is a descriptive qualitative approach with data collection through in-depth interviews, observation, and documentation of MSMEs and Islamic banks. The results show that the implementation of QRIS improves transaction efficiency, accelerates payment processes, and increases MSMEs' trust in Islamic financial services. In addition, digitalization through QRIS also encourages financial inclusion and strengthens the local Islamic economic ecosystem. However, challenges remain in network infrastructure, and technology adaptation for some business actors. This study recommends intensive training and synergy between local governments, Islamic financial institutions, and MSMEs to maximize the use of QRIS in developing the Islamic economy at Padangsidimpuan City